2018
DOI: 10.1080/07380577.2018.1491085
|View full text |Cite
|
Sign up to set email alerts
|

Clients’ Perspectives of the Effectiveness of Home Modification Recommendations by Occupational Therapists

Abstract: This study investigates the effectiveness of home modifications from clients' perspectives. Ten participants who received home assessments and modification recommendations were recruited from a rehabilitation agency. The dimension of home measure and qualitative interviews was conducted. The interviewers were transcribed verbatim and analyzed thematically. Participants found home modifications improved their safety, accessibility, privacy, and occupational performance, especially in performing self-care activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 27 publications
0
23
0
2
Order By: Relevance
“…No articles were excluded due to methodological quality (Appendix S2). Two of the studies were pilot projects (Boman et al, 2007; Gibson et al, 2010) involving convenience samples (Lau et al, 2018; Stark et al, 2009; Taylor et al, 2019). The small sample sizes limited the statistical power of the analyses in two studies (DeForge et al, 2008; Taylor et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No articles were excluded due to methodological quality (Appendix S2). Two of the studies were pilot projects (Boman et al, 2007; Gibson et al, 2010) involving convenience samples (Lau et al, 2018; Stark et al, 2009; Taylor et al, 2019). The small sample sizes limited the statistical power of the analyses in two studies (DeForge et al, 2008; Taylor et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Studies included a broad range of assessment tools (Table 2), including the Canadian Occupational Performance Measure (COPM), Spector‐Katz Index, Timed Up and Go (TUG), Functional Independence Measure (FIM) and the Assessment of Motor and Process Scale (AMPS). Forty seven percent of interventional studies utilised a standardised home safety assessment (Chu et al, 2017; La Grow et al, 2006; Lau et al, 2018; Lockwood et al, 2020; Pighills et al, 2011). The intervention approaches described in the studies are outlined in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence shows that home adaptation schemes contribute to improving quality of life for the disabled and ageing populations (Lau et al, 2018; Hwang et al, 2011) [ 33 , 34 ], but most empirical studies are from the end-users’ rather than from the provider’s perspective (Tural et al, 2020) [ 35 ]. There are relatively fewer studies on the costs of home adaptations (Soares et al, 2020) [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition, studies have investigated effects of inclusion of occupational therapists throughout the home modification process on fall prevention and psychological states such as anxiety of elderly residents. 10 It has been shown that proper home modification supports the successful daily life of the elderly and can reduce accident in house or dependence on caregivers. 11 In spite of such advantages, home modifications rarely occur due to financial burden or willingness to maintain the current level of finance, attitudes of self-denial, absence of information, and experiences.…”
Section: Introductionmentioning
confidence: 99%